Structural, thermal and optical properties of PR³⁺, ER³⁺/DY³⁺ ions singly and doubly doped borotellurite glass system for photonic applications - Abbas, Bashar Khudhair (2020)
Trivalent rare-earth (RE3+) ion doped or codoped glasses have promising technological applications in fiber optical telecommunication systems (1.5 μm region), color display devices, multi-channel wavelength-division multiplexing (WDM) transmission, white (W-LEDs) and solid-state lighting (SSL) emission. In this study, the evaluation of new potential candidate glasses of Pr3+, Er3+/Dy3+ ions singly, and co-doped with a composition of 50B2O3-10 TeO2-10 PbO-10 ZnO-10 Li2O-10 Na2O (borotellurite host glasses) for an optical communication system and SSL/WLEDs has been made. Structural, thermal, and optical properties are investigated of the glass samples were prepared by the melt-quenching method in polished solid and powder forms. Accordingly, from X-ray Diffraction (XRD) measurements, the amorphous-like structure was observed for all the prepared glasses. The presence of various functional groups of borotellurite matrix was confirmed by Attenuated Total Reflectance-Fourier Transform Infrared (ATR-FTIR) and Raman spectra. Thermo- Gravimetric Analysis (TGA) analysis presented low weight loss for all synthesized glasses. From the Differential Scanning Calorimetry DSC profiles the glass transition temperature (Tg), onset crystallization temperature (Tx), and crystallization temperature (Tc) were identified and evaluated as well as the related thermal parameters. Optical absorption characterization was employed for all samples in UVVis.- NIR region. From absorption spectra of Er3+ and Dy3+ singly doped glasses, Judd- Ofelt theory was employed to evaluate their (J-O) intensity parameters (Ωλ, λ=2, 4 and 6) were they are following the same trend Ω2>Ω4>Ω6. Also, the computed ‘χ’=Ω4/Ω6 (spectroscopic quality factor) values are higher than some of the reported glass system. Furthermore, using Judd–Ofelt intensity parameters, the radiative AR (s-1), branching ratio (βR), radiative decay lifetimes τR (μs) for deferent emissions level were computed. Pertaining to the photoluminescence in the visible region, under excitation of 350 nm and 378 nm band, the singly and Er3+/Dy3+ co-doped glasses shows deferent color emission in CIE diagram located at the green, blue and yellow-white region, where these color properties emphasize the potential usage in display, LED and laser applications. Further, under 808 nm excitation, emission peak centered at 1532 nm with an FWHM value of around ~69 which is due to 4I13/2→4I15/2 transition can be observed from all the singly Er3+ and Er3+/Dy3+- codoped glasses. But their NIR fluorescence intensity reduces with the Dy3+ content addition, which indicates the possible ET between Er3+ and Dy3+ ions, suggesting that Dy3+ ions can be used to depopulate Er3+: 4I13/2 level. On the other hand, under 980 nm excitation, 1.0%Er3+ glass possesses the highest NIR emission intensity at 1.532 μm with an FWHM value of 62 nm. NIR emission in 1.0/1.0 Er3+/Dy3+ has completely quenched by the presence of Dy3+ ions, suggesting an efficient ET from Er3+→Dy3+. The singly doped glass (1.0 mol% Er3+) which exhibits the highest intensity at 1.532 μm NIR emission under 980 nm excitation has the highest cross-section value of (2.669 ×10-20 cm2), and an optical gain bandwidth value of (1.65×10-25 cm3) suggested this glass as a potential candidate for 1.532 μm optical fiber laser in telecommunication application systems. Also, the singly and Pr3+/Dy3+ co-doped glasses are evaluated by means of optical properties such as their optical band gap energy (Eg opt) in the UV-Visible region for direct and indirect transitions found to be decreased as the Pr3+ ion concentration increases, which means the increment of donor center content in the glass matrix. Further, the energy level diagram confirmed the mutual energy transfer (Pr3+ Dy3+) under 437 nm and 388 nm excitations. Lastly, the CIE chromaticity results confirm that white warm/neutral as well as reddish-orange light color can be attained by tuning the excitation wavelength. Finally, upon the above findings, the aforementioned glasses (Er3+, Pr3+/Dy3+ singly and doubly doped) are suggested as a useful candidate for the optical communication system in addition to the W-LEDs and SSL applications.